Climate politics and the power of religion - Berry, Evan 1977- (Bloomington, Indiana, USA Indiana University Press, 2022)
"How does our faith affect how we think about and respond to climate change? Climate Politics and the Power of Religion is an edited collection that explores the diverse ways that religion shapes climate politics at the local, national, and international levels. Drawing on case studies from across the globe, it stands at the intersection of religious studies, environment policy, and global politics. From small island nations confronting sea-level rise and intensifying tropical storms to high-elevation communities in the Andes and Himalayas wrestling with accelerating glacial melt, there is tremendous variation in the ways that societies draw on religion to understand and contend with climate change. Climate Politics and the Power of Religion offers 10 timely case studies that demonstrate how different communities render climate change within their own moral vocabularies and how such moral claims find purchase in activism and public debates about climate policy. Whether it be Hindutva policymakers in India, curanderos in Peru, or working-class people's concerns about the transgressions of petroleum extraction in Trinidad-religion affects how they all are making sense of and responding to this escalating global catastrophe"--
Includes bibliographical references and index
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Human Ecology -- Religious aspects -- Case studies; Climatic changes -- Religious aspects -- Case studies; Ecology -- Religious aspects -- Case studies